2007
DOI: 10.1007/s10194-007-0427-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of migraine and pharmacogenomics: some considerations

Abstract: Migraine is a complex disorder caused by a combination of genetic and environmental factors.Although family and twin studies show that there is a genetic component in migraine, no genes predisposing to common forms of the disorder, migraine with and without aura, have been identified. Patients with migraine respond differently to a given drug administered. The efficacy of therapy and the occurrence of adverse drug response are a consequence of individual variability. Genetic profiling of predisposition to migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 50 publications
(45 reference statements)
1
33
0
1
Order By: Relevance
“…These studies recruited patients who mainly suffered from migraine without aura because this subtype of migraine seems to be caused by a combination of genetic and environmental factors, whereas migraine with aura is probably determined largely, or exclusively, by genetic factors [28,29]. It has been suggested that the pathogenic role of the H. pylori infection in migraine, is based on a relationship between the host immune response against the bacterium and the chronic release of vasoactive substances.…”
Section: Discussionmentioning
confidence: 99%
“…These studies recruited patients who mainly suffered from migraine without aura because this subtype of migraine seems to be caused by a combination of genetic and environmental factors, whereas migraine with aura is probably determined largely, or exclusively, by genetic factors [28,29]. It has been suggested that the pathogenic role of the H. pylori infection in migraine, is based on a relationship between the host immune response against the bacterium and the chronic release of vasoactive substances.…”
Section: Discussionmentioning
confidence: 99%
“…Several data suggest that the transcriptional level in these genes and also the role played by environmental factors are important aspects to consider unless assessing a drug's response [2,[10][11][12]. However, since these enzymes act mainly at the hepatic level, analysis of their expression through functional genomics or epigenetic analysis seems unrealistic.…”
Section: The Feasible Diagnostic Setting For Tailored Treatmentmentioning
confidence: 99%
“…The fact that only 50% of migraine patients adequately respond to acute and prophylaxis therapies always suggested questions that only pharmacogenomics (PGx) is able to clarify. The great expectations held by researchers in the field of migraine genetics turned into a widespread disenchantment, since the application goal has been missing [2]. Indeed, after a decade of brilliant genetic evidence on rare forms of migraine, such as familial hemiplegic migraine, very little or almost nothing has been translated to therapeutic management of the most common migraine forms [2][3][4][5][6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The positive associations found with genetic variants in the serotonin transporter have recently not been replicated [142]. A few studies have also considered medication overuse headache as a potential pharmaco-genetic interaction and have found association between this disorder and genetic polymorphisms in the dopamine neurotransmitter system (DAT, MAOA, DRD4, DRD2) and the BDNF [143][144][145] known to predispose patients to drug abuse behaviour. Monoamine oxidase A (MAOA) has also been associated with triptan overuse [146].…”
Section: Headachementioning
confidence: 99%